Approximate target pre-cueing reduces programming quiet eye and movement preparation time: evidence for parameter pre-programming? - Horn, R. R.; Marchetto, J. D. (Research Quarterly for Exercise and Sport, 2021)
Purpose: We examined the effect of target pre-cues on quiet eye duration (QED). If quiet eye (QE) represents the initial and only period for the programming of movement parameters, then the precision of target pre-cues should not affect QED. In contrast, shorter QED after pre-cueing of targets implies some initial programming process to have occurred before QE.